Business Art Business - Parmesani, Loredana; Groninger Museum, Groningen (Milaan : Flash Art Books, 1993)
Plumcake ; Bijl, Guillaume ; Cazal, Philippe ; Ingold Airlines ; Kostabi ; etc.
Business Art Business, Groninger Museum, Groningen, 09.05 - 04.07.1993
boek